(untitled) (Global Journal of Science Frontier Research, 2018)
The wheat crop in the tropical region will be most sufferers because of increased temperature in future. Calibrated and validated DSSAT (CERES-Wheat) model was used to evaluate the impact of increased temperatures (1-3 o C), elevated CO 2 (450 and 550 ppm) levels and radiation changes (5% and 10% increase and decrease) on the yield of wheat in Bangladesh. The highest grain yield of 5194 kg ha -1 was obtained from BARI Gom-28 followed by BARI Gom-27 (4866 kg ha -1 ) and BARI Gom-26 (4573 kg ha -1 ) under existing temperature conditions. Wheat yield at Gazipur increased with elevated atmospheric CO 2 concentration but decreased with the increase in temperature. On an average, 11.95, 18.97 and 22.82 percent yield reductions were observed with 1, 2 and 3-degree rise in temperatures, respectively under ambient CO 2 level at Gazipur. About 2-4% yield compensations are likely if the CO 2 level is increased up to 550 ppm. In Dinajpur area, grain yield of wheat (BARI Gom-28) also reduced by about 6-25% depending on temperature rise.